Mast cell promotes obesity by activating microglia in hypothalamus - Tian, Wen; Wang, Jinghui; Zhu, Yangyang; Zhang, Yi; Chen, Liwei; Hu, Cheng (Frontiers in Endocrinology, 2025)
BackgroundObesity has become a significant public health issue, yet its underlying mechanisms remain complex. The hypothalamus, a crucial part of the central nervous system, plays a vital role in maintaining energy balance. Disruptions in hypothalamic homeostasis can lead to obesity and related metabolic disorders. Recent studies have increasingly focused on the role of intercellular interactions within the hypothalamus in obesity development, though the exact mechanisms are still under investigation. Mast cells, as innate immune cells, have been linked to obesity, but their specific roles and mechanisms require further exploration. This study aims to investigate whether hypothalamic mast cells influence microglia and subsequently affect metabolic homeostasis.MethodsWe conducted experiments to examine the effects of high-fat diets on mast cells in the arcuate nucleus of the hypothalamus. We analyzed the activation of microglia and the activity of POMC neurons in response to mast cell activation. The study involved feeding mice a high-fat diet and then assessing changes in mast cell populations, microglial activation, and neuronal activity in the hypothalamus.ResultsOur findings indicate that high-fat feeding increases the number of mast cells in the arcuate nucleus of the hypothalamus. These mast cells activate microglia, which in turn suppress the activity of POMC neurons. This suppression promotes appetite and reduces energy expenditure, leading to obesity. The results suggest a direct role of hypothalamic mast cells in the regulation of energy balance and obesity development.DiscussionThis study highlights the regulatory role of mast cells in the hypothalamus in the formation of obesity. By activating microglia and influencing POMC neuron activity, mast cells contribute to metabolic dysregulation. These findings provide a new target for the treatment of obesity and related metabolic diseases, emphasizing the importance of hypothalamic immune interactions in metabolic health. Further research is needed to explore the potential therapeutic applications of targeting mast cells in obesity management.